Given the conditional statement:

[tex]\[ p \rightarrow \sim q \][/tex]

Choose the logically equivalent statement.

A. [tex]\( p \rightarrow q \)[/tex]
B. [tex]\( \sim p \rightarrow q \)[/tex]
C. [tex]\( q \rightarrow p \)[/tex]
D. [tex]\( q \rightarrow \sim p \)[/tex]



Answer :

To determine the logically equivalent statement to the conditional statement [tex]\( p \rightarrow \sim q \)[/tex], we can follow a series of logical equivalences and reasoning.

1. Understanding the Implication:
The statement [tex]\( p \rightarrow \sim q \)[/tex] means "if [tex]\( p \)[/tex] then not [tex]\( q \)[/tex]".

2. Using Logical Equivalences:
There's a fundamental equivalence in logic that can help us:
[tex]\[ p \rightarrow q \text{ is equivalent to } \sim q \rightarrow \sim p \][/tex]
This suggests that the implication can be rephrased using its contrapositive. However, instead of directly using this equivalence, we will derive the equivalent form.

3. Rewriting the Condition:
The given statement, [tex]\( p \rightarrow \sim q \)[/tex], can be interpreted as:
- If [tex]\( p \)[/tex] is true, then [tex]\( q \)[/tex] must be false.

4. Finding the Contrapositive:
The contrapositive of the statement [tex]\( p \rightarrow \sim q \)[/tex] is found by negating both parts and swapping them. This means we take:
- [tex]\(\sim(\sim q)\)[/tex], which simplifies to [tex]\( q \)[/tex]
- [tex]\(\sim p\)[/tex]

So, the contrapositive becomes:
[tex]\[ \sim q \rightarrow \sim p \text{ is equivalent to } q \rightarrow \sim p \][/tex]

5. Conclusion:
Based on our logical equivalence transformation, the statement [tex]\( p \rightarrow \sim q \)[/tex] is logically equivalent to [tex]\( q \rightarrow \sim p \)[/tex].

Therefore, the logically equivalent statement to [tex]\( p \rightarrow \sim q \)[/tex] is:
\[
q \rightarrow \sim p
\